2D evaluation of crack openings using smeared and embedded crack models - Gamino, Andre L. [UNESP]; Manzoli, Osvaldo Luis [UNESP]; Antunes de Oliveira e Sousa, Jose Luiz; Bittencourt, Tulio Nogueira (Techno-press, 2010)
This work deals with the determination of crack openings in 2D reinforced concrete structures using the Finite Element Method with a smeared rotating crack model or an embedded crack model In the smeared crack model, the strong discontinuity associated with the crack is spread throughout the finite element As is well known, the continuity of the displacement field assumed for these models is incompatible with the actual discontinuity However, this type of model has been used extensively due to the relative computational simplicity it provides by treating cracks in a continuum framework, as well as the reportedly good predictions of reinforced concrete members' structural behavior on the other hand, by enriching the displacement field within each finite element crossed by the crack path, the embedded crack model is able to describe the effects of actual discontinuities (cracks) This paper presents a comparative study of the abilities of these 2D models in predicting the mechanical behavior of reinforced concrete structures Structural responses are compared with experimental results from the literature, including crack patterns, crack openings and rebar stresses predicted by both models
Keywords: finite elements; fracture mechanics; smeared crack model; embedded crack model